Comparison of oscillatory activity in subthalamic nucleus in Parkinson's disease and dystonia. - Geng, X; Zhang, J; Jiang, Y; Ashkan, K; Foltynie, T; Limousin, P; Zrinzo, L; Green, A; Aziz, T; Brown, P; Wang, S (Elsevier, 2016)
Objectives Deep brain stimulation (DBS) of the subthalamic nucleus (STN) has been successfully used to treat both Parkinson’s disease (PD) and dystonia. Local field potentials (LFPs) recorded from the STN of PD patients demonstrate prominent beta frequency band activity. It is unclear whether such activity occurs in the STN in dystonia, and, if not, whether dystonia has another distinctive neural population activity in the STN. Methods Twelve patients with PD, and eight patients with dystonia underwent DBS electrode implantation targeting the STN. Seven dystonia patients were off medication and one was on aripiprazole and clonazepam. LFPs were recorded from the DBS electrodes in PD in the on/off medication states and in dystonia. Power spectra and temporal dynamics measured by the with Lempel-Ziv complexity of the LFPs were compared among these states. Results Normalised power spectra and Lempel-Ziv complexity of subthalamic LFPs differed between dystonia off and PD on/off, and between PD off and on over the low frequency, beta and high gamma bands. Patients with dystonia and off medication had lower beta power but higher low frequency and high gamma power than PD. Spectral power in the low beta frequency (11-20 Hz) range was attenuated in medicated PD. Conclusion The results suggest that dystonia and PD are characterized by different patterns of oscillatory activities even within the same nucleus, and exaggerated beta activity may relate to hypo-dopaminergic status.